From author to copyist : essays on the composition, redaction, and transmission of the Hebrew Bible in honor of Zipi Talshir - Talshir, Zipora; Werman, Cana (Eisenbrauns, 2015)
Zipi Talshir's work on the evolution, formation, and transmission of the Hebrew Bible throughout her academic career, her remarkable ability to integrate the Septuagint into this research, and her profound understanding of the late books of the Hebrew Bible and the process of canonization are well known and appreciated. In this volume, 21 of Talshir's colleagues and students contribute essays in her honor on these topics that are so close to her heart. A bibliography of her publications and a short biography open and complete this compelling volume presented by renowned authors in the field from all over Europe, Israel, and the U.S.